O direito fundamental de herança e a tributação progressiva - Rabello, Fernanda Souza (2014)
The opening of succession (death event) is classified in our legal system as one of the ways of property transmission. This transmission, immediately operated, transfers the inheritance left by the deceased one free of charges to the heirs, as no effort is required from the heir to effectively receive it. The inheritance, no matter how it is composed, is considered by civil law as property due to the solemn requirements for its transmission. It is a State attribution, with constitutional provision, the power to tax the referred transmission as it results in an asset increase to the beneficiary. The taxation is meant to be, as it is possible, gradually done. Thus, the hability to pay as the criteria of tax fixation is theme of large debates in doctrine and in jurisprudence when it is understood that the inheritance tax is a real tax and because of this couldn't be related to the heir's hability to pay. In this terms, the present work has the objective to analyse the progressive increase as a way of make the hability to pay principal effective in the succession transmission.